Beam Shaping of a Dual-Reflector Antenna Using a Reflectarray as Subreflector and Embedded Unit Cell Patterns - Marzieh Mehri Dehnavi; Jean-Jacques Laurin (IEEE Open Journal of Antennas and Propagation)
This work proposes a phase-only synthesis technique for shaping the beam of a circularly polarized dual-reflector antenna with a subreflector consisting of a reflectarray and a main parabolic reflector. The proposed technique exploits the element patterns of each reflectarray unit cell embedded in the whole system, including a feed horn, a reflectarray, and a main reflector. By using a penalty function that forces only the fitting of the desired and obtained patterns, the algorithm leads to a quasi-random phase distribution on the reflectarray and a poor radiation pattern. A term for minimizing the Laplacian of the phase distribution is added to the penalty function to force a smoothly varying phase distribution on the reflectarray. This modification provides more stable results and yields patterns with desired shapes and regular contours. The beam shaping capability of the algorithm is demonstrated with simulations of a 100-element reconfigurable circularly polarized reflectarray, by controlling independently the 10 dB beamwidth of the antenna in two orthogonal planes The algorithm is also validated experimentally. Beamwidth accuracies vary from 0 to 2.15 degrees.